Chorioretinal venous anastomosis for non-ischemic retinal vein occlusion - Wang, Yucheng; Wang, Shaolong; Wang, Shiwu; Ding, Min; Zhang, Min; Tang, Jiannan; Deng, Aijun (Frontiers in Ophthalmology, 2022)
Retinal vein occlusion (RVO) refers to the occlusion of the central retinal vein or primary and secondary branches caused by multiple factors. Clinical treatments for it include intravitreal or systemic vasodilator application, local usage of steroids and NSAID (non-steroidal anti-inflammatory drugs), thrombolysis, hemodilution, retinal laser photocoagulation, vitrectomy with vascular sheath incision, chorioretinal venous anastomosis (CRVA), and so on. At present, most treatments are aimed at RVO complications, while chorioretinal vein anastomosis can fundamentally reflux retinal vein blood through the choroid by venous vascular remodeling. Reports on the treatment of retinal vein occlusion by chorioretinal anastomosis are numerous in various countries. As a treatment means, CRVA can drain the venous blood, skipping the thrombosis spot, thus partially relieving anatomical vascular occlusion to achieve a therapeutic purpose. In this study, CRVA is evaluated from the aspects of indications, implementation process, postoperative effect evaluation, complications, and combination with anti-VEGF treatment. Based on the development of laser technology and vitrectomy, we hope to further review this treatment and provide a new reference for the clinical treatment of RVO.